Preparation method of novel battery anode material
The ternary lithium dense film layer is formed through the tungsten boat evaporation plating technology, which solves the problem of capacity attenuation of spinel-type LiMn2O4 during the cycle, and achieves a significant increase in battery energy storage and a reduction in cost.
Patent Information
- Application Number
- CN202411599134.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Spinel type LiMn2O4 is susceptible to the influence of preparation processes and conditions, resulting in large capacity attenuation during the cycle, hindering its large-scale application.
The tungsten boat evaporation plating technology is used to accurately control the current and voltage, and a ternary lithium dense film layer is formed, embedded on the aluminum foil to form a new biomass new ternary lithium.
It significantly improves lithium-ion embedded capacity and charge and discharge stability, and battery energy storage can be increased by about 2-3 times, with a cycle life of about 15% higher than that of gel coating, and reduces battery cost.
Smart Images

Figure CN119506783A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new energy batteries, and in particular to a method for preparing a novel battery anode material. Background Art
[0002] Ternary positive electrode material is one of the key materials for lithium-ion batteries. It is composed of elements such as nickel, cobalt, manganese or aluminum. Nickel can improve energy density, cobalt stabilizes the structure and affects the charging and discharging performance, and manganese or aluminum can enhance safety and stability. With its high energy density, good cycle stability and cost-effectiveness, ternary positive electrode material has become mainstream and is widely used in new energy vehicles, power tools, energy storage equipment and other fields, playing an important role in promoting the development of related industries.
[0003] With the expansion of the application field of lithium batteries, the market demand for them is increasing, but their high prices have seriously restricted their large-scale commercialization. At present, the positive electrode materials of lithium-ion batteries are mainly layered structure liCo2, liNiO2, olivine structure liFePO4 and spinel LiMn2O4. However, in actual use, compared with other materials, spinel LiMn2O4 is environmentally friendly and pollution-free, has a high operating voltage, low cost, and can discharge large currents. It is an ideal positive electrode material for power secondary lithium-ion batteries. However, spinel LiMn2O4 is easily affected by the preparation process and conditions, which causes a large capacity decay during the cycle, hindering its large-scale application.
[0004] At present, there are three main types of ternary cathode materials that have been commercially applied, namely LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.4 C0 0.2 Mno 0.4 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2, among which LiNi is the most widely used 1 / 3 Co 1 / 3 Mn 1 / 3 O2. The study found that in the ternary positive electrode material, the three different element components play different roles in the entire material. The presence of Ni increases the specific capacity of the material, but the Ni2+ content cannot be too large. When it is excessive, it will cause ion mixing and reduce the battery capacity retention rate; Co can improve the ionic conductivity of the material, thereby improving the battery's rate cycle performance, but the Co element content cannot be too high, otherwise it will increase the cost; Mn greatly reduces the cost of the material and improves the safety of the battery, but the presence of excessive Mn will damage the material structure, resulting in a reduction in battery capacity. In view of this, we propose a new method for preparing anode materials for batteries. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a novel battery anode material, which solves the problem that spinel LiMn2O4 is easily affected by the preparation process and conditions, causing a large capacity decay during the cycle process, thus hindering its large-scale application.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a new type of battery anode material, including the following materials: a ternary material composed of Li, Ni, Co, and Mn elements as a basic plating material, wherein the atomic number ratio of the four groups of elements is 3:1:1:1, active material, and aluminum foil with a purity of more than 99% and uniform thickness.
[0007] A method for preparing a novel battery anode material comprises the following steps:
[0008] S1: Raw material collection and quality inspection
[0009] Select ternary materials including Li, Ni, Co and Mn with a purity of 99% or more as basic plating materials, active materials, tungsten boats with a length of 5-15cm and an inner diameter of 2-5cm, and aluminum foil with a purity of 99% or more and uniform thickness;
[0010] S2: Equipment preparation and vacuum environment generation
[0011] Use the vacuum pump to evacuate the reaction chamber. First, turn on the rough vacuum pump to reduce the pressure in the reaction chamber to 0.8-1.2 Pa, then switch to the high vacuum pump to continue evacuating until the pressure reaches 1×10 -4 -1×10 -5 Pa vacuum degree, and then oxygen is introduced into the high vacuum reaction chamber through a gas delivery system at a gas flow rate of 10-50sccm;
[0012] S3: Tungsten boat heating and electron beam acceleration
[0013] The voltage and current are gradually increased through the power supply device to heat up the tungsten boat until the temperature of the tungsten boat reaches 1500-2500°C, and at the same time, the electron beam accelerator is turned on to evaporate the ternary material and the active material into a vapor state;
[0014] S4: Film processing and performance improvement verification
[0015] Through tungsten boat seeding, and with the voltage and current control, Li, Ni, Co, and Mn are alternately coated, forming new substances and new ternary lithium on the surface of aluminum foil, and the materials after coating are measured, and a special constant potentiostat is used to verify whether the lithium ion embedding capacity is expanded when the charge and discharge current density is 0.1-1C;
[0016] S5: Physical performance testing and feedback adjustment
[0017] The materials after film coating are subjected to antioxidant time detection and type test, and the parameter data in the vegetation process are adjusted and optimized according to the experimental results.
[0018] Preferably, the proportion of each element in the ternary material in S1 is determined according to the characteristics of the target product, and the proportion of substances in the ternary material is set to x, y, and z respectively, then the value range of x, y, and z can be between 0-1, and satisfy x+y+z=1.
[0019] Preferably, the vacuum reaction chamber used in S2 supports up to 1×10 -5 Pa and below, the voltage adjustment range of the DC power supply equipment used in S2 is 0-1000V, the current adjustment range is 0-50A, and the high-voltage arc discharge device used in S2 can output a voltage between 500-5000V and a discharge current between 1-20A.
[0020] Preferably, the initial voltage in S3 is set to 100-200V, and the current is set to 5-10A, and then gradually adjusted according to the tungsten boat temperature monitoring situation until the tungsten boat temperature reaches 1500-2500°C. The electron beam acceleration device in S3 sets the electron beam acceleration voltage between 200-800V and the acceleration current between 1-10A.
[0021] Preferably, in S3, it is necessary to establish temperature detection characteristic points on the surface of the tungsten boat before heating the tungsten boat, and use an infrared temperature measuring device and a movable bracket to monitor the temperature of the characteristic point area on the surface of the tungsten boat. During the process, the movable bracket is controlled by a motor to rotate and swing, and the main detection area of the infrared temperature measuring device is kept swinging and cyclically monitoring at multiple temperature detection characteristic points according to the set path.
[0022] Preferably, in S3, a preset temperature change curve needs to be set for the overall temperature change state of the tungsten boat, and during the detection process of the infrared temperature measuring device, corresponding regional temperature change curves are generated for each set temperature monitoring feature point, and the actually monitored temperature change curve is compared with the preset temperature change curve to obtain the temperature deviation value curve of each region and feed it back to the monitoring device.
[0023] Preferably, a temperature difference abnormal alarm mechanism is established in S3, and an abnormal alarm is issued when the deviation value of any event in the temperature deviation curve is greater than a set threshold. At the same time, an abnormal alarm is also issued when the temperature difference between multiple temperature detection feature points exceeds the set threshold.
[0024] Preferably, in S3, high-voltage arc discharge is used for collaborative processing. The high-voltage arc discharge device is started, and the discharge voltage is set to 1000-3000V and the discharge current is set to 3-10A. The electron beam acceleration effect generated by the device is used to further enhance the evaporation of the material. At the same time, the secondary electrons are bound to the film material area by means of the restraining effect on the charged particles. During the process, the plasma density is monitored by the plasma diagnostic device Langmuir probe until it reaches 1×10 14 -1×10 16 m -3 .
[0025] Preferably, the physical property test in S5 includes an anti-oxidation time test and a type test, wherein the anti-oxidation time test requires placing the sample in different simulated actual use environments, and regularly detecting the degree of oxidation of the sample to check whether its anti-oxidation time is extended, wherein the type test is carried out under specified temperature cycle and mechanical impact conditions to observe the surface condition of the anode material.
[0026] The present invention provides a method for preparing a novel battery anode material, which has the following beneficial effects:
[0027] 1. The present invention uses aluminum foil as the substrate and adopts a tungsten boat evaporation plating method to precisely control the current and voltage to achieve dense and uniform inlaying of the various element components of the ternary lithium material on the aluminum foil according to the required proportion, so that the dense film layer of the ternary lithium can be controlled to 1μm. The area of the ternary lithium film layer per unit mass is larger than that of the current gel coating method, which can greatly improve the energy storage capacity, and the battery energy storage can be increased by about 2-3 times.
[0028] 2. The present invention innovates the current gel coating method into a tungsten boat evaporation coating method. The elements of the ternary lithium material are alternately interlocked with each other in an atomic state and embedded with the base aluminum foil to form a dense film layer. It has strong flexibility, adhesion and oxidation resistance, and is not easy to expand, crack or fall off during the charge and discharge process. The cycle life is about 15% higher than that of the gel coating method.
[0029] 3. The evaporation plating method of the present invention can accurately control the evaporation and embedding amount of each element of the ternary lithium-based material, and replace the precious metal Co with a small amount of Ni and Mn, thereby reducing the cost of the battery. In addition, the ternary lithium film layer formed by the evaporation plating method has lower quality per unit volume than the gel coating method. If "1μm new ternary lithium film layer + 6μm aluminum foil" is used to replace "100μm mixed layer + 6μm aluminum foil", the mass production efficiency and cost of the new ternary positive electrode material with the same energy storage capacity can be reduced by about 10%.
[0030] 4. In the present invention, the temperature of multiple characteristic point areas on the surface of the tungsten boat is monitored by an infrared temperature measuring device, and the actual temperature change curves of the multiple characteristic point areas detected are compared with the preset temperature change curves, so as to intuitively display the temperature change state of the entire tungsten boat, and when abnormal temperature differences and abnormal temperature changes occur, the controller is warned through the abnormal alarm program to avoid the abnormal state during the heating process affecting the quality of the final battery anode. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The following is a flow chart of the preparation method of the anode material;
[0032] Figure 2 It is a schematic diagram of the processing process inside the reaction chamber of the present invention;
[0033] Figure 3 It is a schematic diagram of the crystal structure of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example:
[0036] A new type of battery anode material, including the following materials: a ternary material composed of Li, Ni, Co, and Mn elements as a basic plating material, wherein the atomic number ratio of the four groups of elements is 3:1:1:1, an active material, an aluminum foil with a purity of more than 99% and uniform thickness
[0037] Please see attached Figure 1 - Attachment Figure 3 The present invention provides a method for preparing a novel battery anode material, comprising the following steps:
[0038] S1: Raw material collection and quality inspection
[0039] Select ternary materials including Li, Ni, Co and Mn with a purity of 99% or more as basic plating materials, active materials, tungsten boats with a length of 5-15cm and an inner diameter of 2-5cm, and aluminum foil with a purity of 99% or more and uniform thickness;
[0040] S2: Equipment preparation and vacuum environment generation
[0041] Use the vacuum pump to evacuate the reaction chamber. First, turn on the rough vacuum pump to reduce the pressure in the reaction chamber to 0.8-1.2 Pa, then switch to the high vacuum pump to continue evacuating until the pressure reaches 1×10 -4 -1×10 -5 Pa vacuum degree, and then oxygen is introduced into the high vacuum reaction chamber through a gas delivery system at a gas flow rate of 10-50sccm;
[0042] S3: Tungsten boat heating and electron beam acceleration
[0043] The voltage and current are gradually increased through the power supply device to heat up the tungsten boat until the temperature of the tungsten boat reaches 2000°C. At the same time, the electron beam accelerator is turned on to evaporate the ternary material and the active material into a vapor state;
[0044] S4: Film processing and performance improvement verification
[0045] Through tungsten boat seeding, combined with voltage and current control, Li, Ni, Co, and Mn are alternately coated to form new substances, new ternary lithium, on the surface of aluminum foil. The materials after coating are measured, and a special constant potentiostat is used to detect the lithium ion embedding capacity under different charge and discharge conditions.
[0046] S5: Physical performance testing and feedback adjustment
[0047] The materials after film coating are subjected to antioxidant time detection and type test, and the parameter data in the vegetation process are adjusted and optimized according to the experimental results.
[0048] The proportion of each element in the ternary material in S1 is determined according to the characteristics of the target product. The proportion of substances in the ternary material is set to x, y, and z respectively. The value range of x, y, and z can be between 0 and 1, and x+y+z=1 is satisfied.
[0049] The vacuum chamber used in S2 supports up to 1×10 -5 Pa and below, the voltage adjustment range of the DC power supply equipment used in S2 is 0-1000V, the current adjustment range is 0-50A, and the high-voltage arc discharge device used in S2 can output a voltage between 500-5000V and a discharge current between 1-20A.
[0050] The initial setting voltage in S3 is 100-200V, and the current is 5-10A, and then gradually adjusted according to the tungsten boat temperature monitoring situation until the tungsten boat temperature reaches 2000°C. The electron beam acceleration device in S3 sets the electron beam acceleration voltage between 200-800V and the acceleration current between 1-10A.
[0051] In the S3, it is necessary to establish temperature detection characteristic points on the surface of the tungsten boat before heating the tungsten boat, and use an infrared temperature measuring device and a movable bracket to monitor the temperature of the characteristic point area on the surface of the tungsten boat. During the process, the movable bracket is controlled by a motor to rotate and swing, and the main detection area of the infrared temperature measuring device is kept swinging and cyclically monitoring at multiple temperature detection characteristic points according to the set path.
[0052] In the above S3, a preset temperature change curve needs to be set for the overall temperature change state of the tungsten boat. At the same time, during the detection process of the infrared temperature measuring device, corresponding regional temperature change curves are generated for each set temperature monitoring feature point, and the actually monitored temperature change curve is compared with the preset temperature change curve to obtain the temperature deviation value curve of each region and feed it back to the monitoring device.
[0053] In S3, a temperature difference abnormal alarm mechanism is established, and an abnormal alarm is issued when the deviation value of any event in the temperature deviation curve is greater than a set threshold. At the same time, an abnormal alarm is also issued when the temperature difference value between multiple temperature monitoring feature points exceeds the set threshold.
[0054] In S3, high-voltage arc discharge is used for collaborative processing. The high-voltage arc discharge device is started, and the discharge voltage is set at 1000-3000V and the discharge current is set at 3-10A. The electron beam acceleration effect generated by the device is used to further enhance the evaporation of the material. At the same time, the secondary electrons are bound in the film material area by means of the restraining effect on the charged particles. During the process, the plasma density is monitored by the plasma diagnostic device Langmuir probe until it reaches 1×10 15 m-3.
[0055] In S4, a constant potential instrument is used to verify whether the lithium ion embedding capacity is expanded when the charge and discharge current density is 0.1-1C. During the process, a positive electrode material prepared by gel coating in the prior art is introduced as a control group, and the following experimental data are obtained by comparison:
[0056] Experiment number Cathode material preparation method Charge and discharge current density Initial value of lithium ion insertion capacity 1 Tungsten boat evaporation coating 0.1(C) 150.6 (mAh / g) 2 Tungsten boat evaporation coating 0.5(C) 130.4 (mAh / g) 3 Tungsten boat evaporation coating 1(C) 120.1(mAh / g) 4 Gel coating 0.1(C) 70.7 (mAh / g) 5 Gel coating 1(C) 50.6 (mAh / g)
[0057] According to the above experiments, the positive electrode material prepared by tungsten boat evaporation shows a high lithium ion embedding capacity at different charge and discharge current densities. Specifically, when the charge and discharge current density is 0.1C, the initial value of the lithium ion embedding capacity reaches 150.6mAh / g, and when the current density is increased to 0.5C, the lithium ion embedding capacity remains at 130.4mAh / g. Even at a higher current density of 1C, the lithium ion embedding capacity is 120.1mAh / g, which shows that the positive electrode material prepared by tungsten boat evaporation has good electrochemical properties and high charge and discharge stability.
[0058] In contrast, the cathode material prepared by gel coating performed poorly under the same conditions. At a current density of 0.1C, the initial value of lithium ion insertion capacity was only 70.7mAh / g, and it further decreased to 50.6mAh / g at a current density of 1C. This shows that the electrochemical performance and stability of the cathode material prepared by gel coating at high current density are not as good as those prepared by tungsten boat evaporation.
[0059] In summary, tungsten boat evaporation technology has significant advantages in preparing new battery anode materials, and can effectively improve the lithium ion embedding capacity and charge and discharge stability of the materials. Therefore, this technology is expected to be widely used in the field of high energy density batteries.
[0060] The physical property test in S5 includes an anti-oxidation time test and a type test, wherein the anti-oxidation time test requires placing the sample in different simulated actual use environments and regularly testing the oxidation degree of the sample to check whether its anti-oxidation time is extended, wherein the type test is carried out under specified temperature cycle and mechanical impact conditions to observe the surface condition of the anode material;
[0061] Regarding the oxidation time of the sample, in this experiment, when the surface of the anode material made by gel coating or the anode material made by evaporation plating produces oxidation changes, the oxidation time is calculated, and the extension is obtained by comparing the oxidation time of the anode material made by evaporation plating and the anode material made by gel coating. The following is the experimental data:
[0062]
[0063]
[0064] According to the above experiments, by comparing the anti-oxidation time of the anode materials made by the gel coating method and the evaporation coating method under different environmental conditions, it can be clearly seen that the gel coating method shows a longer anti-oxidation time under various conditions. Specifically, the anti-oxidation time of the gel coating method was extended by 11.7% in an environment with a temperature of 50°C and a humidity of 80%; by 13.7% in an environment with a temperature of 25°C and a humidity of 80%; by 12.2% in an environment with a temperature of -20°C and a humidity of 20%; by 13.5% in an environment with a salt spray concentration of 5%; by 13.7% in an environment with high-intensity sunlight and room temperature; by 14.4% in an environment with low-intensity sunlight and room temperature; and by 13.5% in an environment with a medium concentration of simulated pollutants.
[0065] These data show that the gel coating method can effectively improve the anti-oxidation performance of the anode material under different environmental conditions, thereby extending the service life of the battery. In addition, the experimental results also show that under conditions of low sunlight intensity, the anti-oxidation time of the gel coating method is most significantly extended, reaching 14.4%. This is because under lower sunlight intensity, the protective layer formed on the surface of the anode material by the gel coating method is more stable, thereby effectively slowing down the process of the oxidation reaction.
[0066] In summary, the gel coating method has significant advantages in preparing new battery anode materials, especially in improving the antioxidant performance. Therefore, this method has a high promotion value in practical applications, especially in the field of batteries that require long-term stable operation.
[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A new type of battery anode material, characterized in that: The following materials are included: a ternary material composed of Li, Ni, Co, and Mn elements as a basic plating material, wherein the atomic number ratio of the four groups of elements is 3:1:1:1, active material, and aluminum foil with a purity of more than 99% and uniform thickness.
2. A method for preparing a new type of battery anode material, characterized in that: The following steps are involved: S1: Raw material collection and quality inspection Select ternary materials including Li, Ni, Co and Mn with a purity of 99% or more as basic plating materials, active materials, tungsten boats with a length of 5-15cm and an inner diameter of 2-5cm, and aluminum foil with a purity of 99% or more and uniform thickness; S2: Equipment preparation and vacuum environment generation Use the vacuum pump to evacuate the reaction chamber. First, turn on the rough vacuum pump to reduce the pressure in the reaction chamber to 0.8-1.2 Pa, then switch to the high vacuum pump to continue evacuating until the pressure reaches 1×10 -4 -1×10 -5 Pa vacuum degree, and then oxygen is introduced into the high vacuum reaction chamber through a gas delivery system at a gas flow rate of 10-50sccm; S3: Tungsten boat heating and electron beam acceleration The voltage and current are gradually increased through the power supply device to heat up the tungsten boat until the temperature of the tungsten boat reaches 1500-2500°C, and at the same time, the electron beam accelerator is turned on to evaporate the ternary material and the active material into a vapor state; S4: Film processing and performance improvement verification Through tungsten boat seeding, and with the voltage and current control, Li, Ni, Co, and Mn are alternately coated, forming new substances and new ternary lithium on the surface of aluminum foil, and the materials after coating are measured, and a special constant potentiostat is used to verify whether the lithium ion embedding capacity is expanded when the charge and discharge current density is 0.1-1C; S5: Physical performance testing and feedback adjustment The materials after film coating are subjected to antioxidant time detection and type test, and the parameter data in the vegetation process are adjusted and optimized according to the experimental results.
3. The method for preparing a novel battery anode material according to claim 2, characterized in that: The proportion of each element in the ternary material in S1 is determined according to the characteristics of the target product. The proportion of substances in the ternary material is set to x, y, and z respectively. The value range of x, y, and z can be between 0 and 1, and x+y+z=1 is satisfied.
4. The method for preparing a novel battery anode material according to claim 2, characterized in that: The vacuum chamber used in S2 supports up to 1×10 -5 Pa and below, the voltage adjustment range of the DC power supply equipment used in S2 is 0-1000V, the current adjustment range is 0-50A, and the high-voltage arc discharge device used in S2 can output a voltage between 500-5000V and a discharge current between 1-20A.
5. The method for preparing a novel battery anode material according to claim 2, characterized in that: The initial voltage setting in S3 is 100-200V, and the current is 5-10A, and then gradually adjusted according to the tungsten boat temperature monitoring situation until the tungsten boat temperature reaches 1500-2500°C. The electron beam acceleration device in S3 sets the electron beam acceleration voltage between 200-800V and the acceleration current between 1-10A.
6. The method for preparing a novel battery anode material according to claim 2, characterized in that: In the S3, it is necessary to establish temperature detection characteristic points on the surface of the tungsten boat before heating the tungsten boat, and use an infrared temperature measuring device and a movable bracket to monitor the temperature of the characteristic point area on the surface of the tungsten boat. During the process, the movable bracket is controlled by a motor to rotate and swing, and the main detection area of the infrared temperature measuring device is kept swinging and cyclically monitoring at multiple temperature detection characteristic points according to the set path.
7. The method for preparing a novel battery anode material according to claim 6, characterized in that: In the above S3, a preset temperature change curve needs to be set for the overall temperature change state of the tungsten boat. At the same time, during the detection process of the infrared temperature measuring device, corresponding regional temperature change curves are generated for each set temperature detection feature point, and the actually monitored temperature change curve is compared with the preset temperature change curve to obtain the temperature deviation value curve of each region and feed it back to the monitoring device.
8. The method for preparing a novel battery anode material according to claim 7, characterized in that: In S3, a temperature difference abnormal alarm mechanism is established, and an abnormal alarm is issued when the deviation value of any event in the temperature deviation curve is greater than a set threshold. At the same time, an abnormal alarm is also issued when the temperature difference value between multiple temperature detection feature points exceeds the set threshold.
9. The method for preparing a novel battery anode material according to claim 2, characterized in that: In S3, high-voltage arc discharge is used for collaborative processing. The high-voltage arc discharge device is started, and the discharge voltage is set at 1000-3000V and the discharge current is set at 3-10A. The electron beam acceleration effect generated by the device is used to further enhance the evaporation of the material. At the same time, the secondary electrons are bound in the film material area by means of the restraining effect on the charged particles. During the process, the plasma density is monitored by the plasma diagnostic device Langmuir probe until it reaches 1×10 14 -1×10 16 m -3 .
10. The method for preparing a novel battery anode material according to claim 2, characterized in that: The physical property test in S5 includes an anti-oxidation time test and a type test. The anti-oxidation time test requires placing the sample in different simulated actual use environments and regularly testing the degree of oxidation of the sample to check whether its anti-oxidation time is extended. The type test is carried out under specified temperature cycle and mechanical impact conditions to observe the surface condition of the anode material.